Geographic distance and state's grip: Information asymmetry, state inattention, and firm implementation of state policy - YANG, Xiyi (Institutional Knowledge at Singapore Management University, 2023)
In this study, we develop the argument that geographic distance between the state and local governments undermines the state's capacity to influence the implementation of state policies by local organizations. Drawing from information economics and the attention-based view, we propose that physical distance reduces the state's monitoring effectiveness through two interrelated mechanisms: information asymmetry and state leaders' inattention to distant issues. Using data of Chinese public firms' implementation of environmental activities between 2008 and 2016, we find that firms conduct fewer environmental activities required by the state when they are regulated by local governments that are more geographically distant to Beijing. This distance effect is, however, attenuated in regions with higher levels of gross domestic product growth and Internet activism. Furthermore, firm characteristics that draw the direct attention of state leaders and provide alternative information channels-namely, firm visibility and government subsidy received-negatively moderate the effect of geographic distance. This study contributes to the literatures by identifying a geography-based view of state capacity in shaping organizational behaviors and its underlying mechanisms.